Description of Culicoides lisicarruni (Diptera: Ceratopogonidae), a new species from Cundinamarca, Colombia - Moncada, Ligia (2010)
A new species of Culicoides of the subgenus Diphaomyia Vargas from high altitudes of the Andes in Colombia is described and photographied. The species is compared with its similar congener Culicoides marinkellei Wirth & Lee. Data on the collecting site and notes on the species daily activity are also provided.